Perlindungan Hukum Bagi Penerima Waralaba (Franchisee) Dalam Perjanjian Waralaba - Ni Nyoman Triana Suskendariani (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
The issue of legal protection for franchise recipients is a very important problem at this time, this needs to be examined because the protection has a very important impact on the franchisee. Protection of the interests of the recipient of the franchise is very necessary because in reality the franchisee is always the party that is harmed.